c - Gyeltshen, Zhmpoen Dorji; National Library (Bhutan) (Thimphu : National Library of Bhutan, 1999)
Manual of etiquette for the Bhutanese citizen.
In Dzongkha.
Keywords: Bhutan -- Social life and customs; Etiquette -- -- Bhutan -- -- Handbooks, manuals, etc